Validation of a simplified oral indicator for home care nurses to refer older people to dental care professionals - Lina F. Weening-Verbree; Annemarie A. Schuller; Wim P. Krijnen; Cees P. van der Schans; Sytse U. Zuidema; Johannes S. M. Hobbelen (Acta Odontologica Scandinavica, 2024)
Objectives: This study aims to explore the identification of older people in need of dental consultation, with a Simplified Oral Indicator (SOI) used by home care nurses (HCNs) and with the Geriatric Oral Health Assessment Index (GOHAI-NL) completed by older people themselves, compared with the Oral Health Assessment Tool (OHAT-NL), performed by dental hygienists.